The determination of the solubility of mercurous chloride at 25Â°C - Dry, Mark Eberhard (Rhodes University, Faculty of Science, Department of Chemistry, 1954)
After the publication of the paper by Gledhill and Malan in which precision conductance techniques were used for the first time in the determination of the solubility of silver chloride, Dr. N.H. Perton of Christchurch College, New Zealand, wrote to Gledhill and suggested that the same methods might be rewarding if applied to the determination of the solubility of mercurous chloride. A review of the Chemical literature showed that the values for the solubility of mercurous chloride were not at all consistent. Into., p. 1
Keywords: Mercuric chloride